Biotransformação da Quercetina e produção de metabólitos ativos por Penicillium sp. 392 (GhG2 2.1) isolado de Gustavia elliptica M. (lecythidaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Biotransformation is an effective tool for modifying natural structures and producing bioactive products of industrial interest. Many microorganisms have been used in processes of biotransformation of natural products, originating metabolites already known or new, including with the use of endophytic fungi. In this regard, it was proposed to obtain bioactive derivatives of quercetin through biotransformation performed by Penicillium sp. From preserved samples of Penicillium sp. Biotransformation of quercetin was carried out in different media and conditions. Quercetin was added to each sample with a microorganism (except in the negative controls), containing mineral medium, buffer pH 7.5 and water. After biotransformation, these samples were submitted to spectrophotometric analyzes in HPLC MS-DAD and 1D and 2D NMR. Tests were performed to detect anti-inflammatory, anti-glycation, antimicrobial activity and evaluation of cytotoxicity. The biotransformation of quercetin in the mineral medium was observed after two days of induction of the molecule, in the MBt and MicMBt samples, when submitted to the ideal parameters of pH 7.5; stirring time and temperature from 24h to 48h after adding quercetin at 28 °C and 120 rpm; concentration of quercetin substrate of 100 mg/100 ml; sugar level in the culture medium reduced by 1/4; level of quantity of cells in the media (18x108/ml) and cultivation from conidia suspension. In the tests for antimicrobial testing, the samples showed low inhibitory activity with a halo of 6 mm to 12 mm in gram-positive bacteria and 8 mm in gram-negative bacteria at a concentration of 5 mg/ml. The anti-glycation assay, the two fractions containing the major substance identified had a high rate of inhibition in the fructose pathway, with IC50 values for MicMBt 11.00±0.75 and for MBt 17.17 ± 0.51 μg/ml, when compared to the aminoguanidine standard (28.60±1.35 μg/ml). In anti-inflammatory activity, fractions were shown to inhibit macrophage activation when monitored for nitric oxide production. Regarding the cytotoxicity, the fractions showed low toxicity up to a concentration of 50 μg/ml. The biotransformation of quercetin by Penicillium sp (392) produced as major compounds the methyl 3,4-dihydroxybenzoate ester and the substance 2 - ((3,4-dihydroxybenzoyl)oxy)–4,6-dihydroxy benzoic acid, identified as major molecules, which were responsible for anti-glycant and anti-inflammatory activities in vitro models. The present work was a pioneer in the study of biotransformation of flavonoids by endophytic fungi from the Amazon Region, whose main perspective is to produce derivatives that are potentially active in biological models.
Keywords: Biotransformação; Compostos fenólicos; Penicillium sp; Atividade antiglicante; Fungo endofítico; CIÊNCIAS BIOLÓGICAS; Bioconversão; Fungo endofítico; Antiglicante; Anti-inflamatório; Compostos fenólicos